BENTUK KLAUSULA-KLAUSULA BAKU DALAM PERJANJIAN KREDIT BANK - Marsidah, Marsidah (Solusi, 2019)
Every bank loan must be stated in a written credit agreement. Bank credit agreement is a standard agreement with the contents or clauses of the bank credit agreement that has been standardized and set forth in the form of a form (blank), but not bound in a certain form. The validity of the credit agreement lies in public acceptance and business traffic to facilitate standard agreements in general is an unequal clause between the creditors (banks) and debtors (customers) which causes the principle of balance in the agreement as if not fulfilled. Based on the foregoing, the formulation of the problem in this paper is What are the standard clauses in a bank credit agreement. While the purpose of this paper is to describe, know and understand the forms of standard clauses in bank credit agreements. In connection with the problem under study are the forms of standard clauses in bank credit agreements including credit facilities, interest rates, bank power, bank repayment guarantees, precedent loans, credit collateral, affirmative and negative covenants, bank actions in saving loans, event of default, legal choice, start the entry into force of the credit agreement.